Phenotypic Characterization and Virulence Profiling of Enterobacter Species Isolated from Clinical Specimens in Thi-Qar Province, Iraq - Sekhi, Ahmed Hasan; Jaber, Amany Shakeir (Medical Science Journal for Advance Research, 2025)
Background: Enterobacter species are nosocomial pathogens associated with urinary tract infections (UTIs), wound infections, and burns. Their virulence mechanisms, including biofilm formation, capsule production, and colonization factors, contribute to their pathogenicity and antimicrobial resistance. Objective: This study aimed to isolate and identify Enterobacter species from clinical samples (urine, wounds, and burns) in Thi-Qar province, Iraq, and to phenotypically evaluate their virulence factors. Methods: A total of 120 clinical samples (67 urine samples, 32 wound swabs, and 21 burn swabs) were collected. The isolates were cultured on MacConkey agar and identified using biochemical tests and VITEK-2. Virulence factors were assessed using the following phenotypic assays: biofilm formation (tube method), CFA expression (slide agglutination), capsule detection (India ink), and hemolysis (blood agar). Results: Among 42 Enterobacter isolates, E. cloacae (54.8%) predominated over E. sakazakii (40.4%) and E. aerogenes (4.8%). Urine samples yielded the highest isolates (71.4%), with E. cloacae predominant (47.6%), while E. sakazakii was more frequent in wounds (16.7%). Phenotypic analysis revealed non-hemolytic isolates (87–82.4% for E. cloacae and E. sakazakii), high capsule prevalence (87% and 82.4%), and biofilm formation (73.9% and 76.5%). E. sakazakii exhibited significantly higher CFA I (76.5% vs. 30.4%) and CFA III (88.2% vs. 52.2%) than E. cloacae (p < 0.05). Conclusion: Enterobacter species, particularly E. cloacae and E. sakazakii, are significant pathogens in clinical settings, with distinct virulence profiles that influence their niche preferences. The high prevalence of capsules and biofilms underscores their roles in persistence and antibiotic resistance